1991
DOI: 10.1029/91jd00269
|View full text |Cite
|
Sign up to set email alerts
|

Trace gas exchange above the floor of a deciduous forest: 1. Evaporation and CO2 efflux

Abstract: The eddy correlation method has great potential for directly measuring trace gas fluxes at the floor of a forest canopy, but a thorough validation study has not been yet conducted. Another appeal of the eddy correlation method is its ability to study processes that regulate and modulate gas exchange between the soil/litter complex and the atmosphere that cannot be probed with chambers. In this paper we report on eddy correlation measurements of water vapor, sensible heat, and carbon dioxide exchange that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(117 citation statements)
references
References 60 publications
5
111
0
1
Order By: Relevance
“…This often leads to an underestimation of understorey CO 2 efflux when compared to chamber measurements (Norman et al, 1997;Kabwe et al, 2005), although some authors (Law et al, 1999) found a good agreement between both methods. However, averaging half-hourly values over several days should decrease the errors caused by the presence of heterogeneities under forest canopies (Baldocchi and Meyers, 1991).…”
Section: Seasonal Variation In Carbon Dioxide Fluxesmentioning
confidence: 99%
“…This often leads to an underestimation of understorey CO 2 efflux when compared to chamber measurements (Norman et al, 1997;Kabwe et al, 2005), although some authors (Law et al, 1999) found a good agreement between both methods. However, averaging half-hourly values over several days should decrease the errors caused by the presence of heterogeneities under forest canopies (Baldocchi and Meyers, 1991).…”
Section: Seasonal Variation In Carbon Dioxide Fluxesmentioning
confidence: 99%
“…For the methods to work, trace gas species should not have significantly different vertical distributions of sources and sinks. Furthermore, the trace gas in question should be inert over the timescale of the flux-gradient measurement, meaning that the timescale of turbulence (200-300 s in such ecosystems) should not exceed the timescale of chemical reactions Baldocchi and Meyers, 1991).…”
Section: Flux-gradient Methodsmentioning
confidence: 99%
“…Counter-gradient transport of heat, momentum, and trace gases has been documented beneath plant canopies and may severely compromise fluxgradient methods (Shaw, 1977;Raupach and Thom, 1981;Amiro 1990;Baldocchi and Meyers, 1991). On the other hand, flux-gradient methods have been preferred over eddy covariance techniques for measuring surface-atmosphere fluxes within a few meters of the surface layer (Fitzjarrald and Lenschow, 1983;Gao et al, 1991;de Arellano and Duynkerke, 1992;Wagner-Riddle et al, 1996;Taylor et al, 1999;Dunn et al, 2009).…”
Section: Flux-gradient Methodsmentioning
confidence: 99%
See 2 more Smart Citations